The reality of the right to participate in the kindergarten from the viewpoint of the teachers "A field stady in Lattakia city" - Terko, Mohammad; Nasser, Rasha (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research aims to identify the reality of the right to participate in the kindergarten of Lattakia, from the viewpoint of the teachers; it also aims to identify the differences in their views about the reality of the right to participate in the kindergarten of Lattakia according to (scientific and educational qualification, years of experience, and training courses). This research adopts the descriptive approach, and it uses a questionnaire that consists of (36) phrases as a tool to collect data from the sample of the research which targets of (230) teachers in the kindergarten of Lattakia (2017- 2018). The results have shown that: 1- Lattakia kindergartens provide children with the right of getting information in the first place, followed by the right of expressing their opinions and listening to them. 2- Kindergartens care about providing different resources in getting information (pictures, books, stories, and others educational aids…). 3- There are statistical differences in the viewpoints of kindergartens teachers in regard to children right in participating in kindergartens, these differences are due to the scientific and educational qualification between post-graduate studies teachers and teachers who hold a diploma in education in favor of master and doctoral degrees teachers. According to training variable, differences came in favor of the teachers who attended training courses in kindergartens.